Design, Fabrication and Properties of the Multimode Polymer Planar 1 x 2 Y Optical Splitter - Prajzler, Vaclav; Pham, Ngoc Kien; Spirkova, Jarmila (Společnost pro radioelektronické inženýrství, 2012)
We report about design, fabrication and measurement of the properties of multimode 1 x 2 optical planar power splitter. The splitters were designed with help of OptiCAD software using ray tracing method. The dimensions of the splitters were then optimized for connecting standard Plastic Optical Fiber. Norland Optical Adhesives glues were used as optical waveguide layers and the design structures were completed by CNC engraving on Poly(methyl methacrylate) or Poly(methylmethacrylimide) substrate. The devices have the insertion loss around 7.6 dB at 650 nm and the coupling ratio was 52:48.
Keywords: Multimode 1x2 splitter; optical planar waveguide; polymer; ray tracing